Hypersurfaces with Lr-Pointwise 1-Type Gauss Map - Akram Mohammadpouri (Журнал математической физики, анализа, геометрии, 2018)
In this paper, we study hypersurfaces in Еⁿ⁺¹ whose Gauss map G satisfies the equation LrG = f(G + C) for a smooth function f and a constant vector C, where Lr is the linearized operator of the (r+1)-st mean curvature of the hypersurface, i.e., Lr(f) = Tr(Pr ○∇²f) for f ∊ C∞(M), where Pr is the r-th Newton transformation, ∇²f is the Hessian of f, LrG = (LrG₁, . . . ,LrGn₊₁) and G = (G₁, . . . ,Gn₊₁). We focus on hypersurfaces with constant (r + 1)-st mean curvature and constant mean curvature. We obtain some classification and characterization theorems for these classes of hypersurfaces. У статтi вивчаються гiперповерхнi в Еⁿ⁺¹ гауссове вiдображення G яких задовольняє рiвняння LrG = f(G + C) для гладкої функцiї f i постiйного вектора C, де Lr є лiнеаризованим оператором (r + 1)-ої середньої кривизни гiперповерхнi, тобто Lr(f) = Tr(Pr ○∇²f) для f ∊ C∞(M), а Pr є r-им перетворенням Ньютона, ∇²f є гессiаном f, LrG = (LrG₁, . . . ,LrGn₊₁) i G = (G₁, . . . ,Gn₊₁). Наша увага зосереджена на гiперповерхнях з постiйною (r+1)-ою середньою кривизною i постiйною середньою кривизною. Для цих класiв гiперповерхонь отримано теореми класифiкацiЁ i характеризацiї.